2005
DOI: 10.1111/j.1478-4408.2005.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing of cationised cotton using nanoscale pigment dispersions

Abstract: Cotton modifi ed with a cationic reagent has been dyed by an exhaustion process using nanoscale pigment dispersions. Pigment uptake, colour yield and fastness properties on cotton were measured. Uptake of pigment was found to be closely related to the concentration of cationic reagent, pH of the pretreatment bath, pretreatment temperature and time of cationisation. These factors also infl uenced the fastness properties of the fabric. Nanoscale pigment dispersions gave a much higher colour yield than convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Such an approach could be achieved if the nanoparticles can be reduced to a small enough size and the particles can be dispersed well to avoid aggregation of the nanoparticles in dye baths. Exhaust dyeing of cationized cotton with nanoscale pigment dispersion has recently been achieved and the results indicated that the dyeings obtained have better soft handle and more brilliant shade with reduced pigment requirement than those obtained with a conventional pigment dispersion (Fang et al, 2005). Ultrasonic energized dyeing conditions for neem leaves gives better dye uptake, uniform dyeing, better light and wash fastness on cotton fabric (Senthikumar et al, 2002).…”
Section: Non-conventional Dyeing Methodsmentioning
confidence: 99%
“…Such an approach could be achieved if the nanoparticles can be reduced to a small enough size and the particles can be dispersed well to avoid aggregation of the nanoparticles in dye baths. Exhaust dyeing of cationized cotton with nanoscale pigment dispersion has recently been achieved and the results indicated that the dyeings obtained have better soft handle and more brilliant shade with reduced pigment requirement than those obtained with a conventional pigment dispersion (Fang et al, 2005). Ultrasonic energized dyeing conditions for neem leaves gives better dye uptake, uniform dyeing, better light and wash fastness on cotton fabric (Senthikumar et al, 2002).…”
Section: Non-conventional Dyeing Methodsmentioning
confidence: 99%
“…[1] Considering energy saving and environmental protection, the application of pigment coatings in textiles has been receiving growing attention from researchers and manufacturers. However, traditional pigment coatings can not satisfy the demand of textile industry for their large particles and poor stability and color performance that greatly limit the organic pigment application in textiles.…”
Section: Effects Of Process Conditions On Properties Of Nanoscale Orgmentioning
confidence: 99%
“…Nano-particles exhibit better affinity to fabrics and lead to an increase in the durability of their functions, such as water repellence, wrinkle resistance, dyeability with no effect on breathability or hand feel (Wong et al, 2006). Compared with conventional pigments, nano-scaled pigment dispersion provide better soft handle and more brilliant shades (Fang et al, 2005;Wu et al, 2006). Nanotechnology also includes the introduction of nano-particles into a macroscopic material to form nano-composites, which exhibit drastically enhanced properties, like dyeability.…”
Section: Nanotechnologymentioning
confidence: 99%